Analisis Sistem Keamanan Alat Pendeteksi Kebocoran Gas Berbasis Nodemcu Dengan Notifikasi Android - Afifah Dela Anggita; Saprudin Saprudin (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2022)
At this time, LPG gas is very important in household needs because it has a relatively cheap price and is easy to use. On the other hand, the nature of LPG gas is flammable and there are many problems such as gas leaks, so a gas leak detection security system is made that can provide automatic warnings in the form of notifications from a distance using the development model Waterfall. Model Waterfall is a model that is systematic and sequential approach in software development begins with the user's needs, stages of design, modeling, construction, delivery of the system to the user and ends with the resulting software is complete. The results of this study found that the android application that was designed can provide information in the form of notifications about gas leaks accurately from a distance. Because the board NodeMCU, MQ-6 gas sensor, LCD and buzzer connected to this system always use electricity, it is necessary to add batteries as backup power and add tools to monitor house conditions that can trigger fires and add electrical power control features as handling first.